Non-racialism in South Africa The life and times of Neville Alexander - Zinn, Allan (African Sun Media, 2016)
At the time of his death in August 2012 Neville Alexander was undoubtedly one of South Africa's foremost proponents of the philosophy of non-racialism. He had devoted his life to fighting against the evils of racism, sexism and economic injustice. He understood how these social realities not only divided but also ranked human beings in terms of human worth and value. He saw how these realities diminished the whole society, both the perpetrators and victims. And so he gave over his life as a scholar and a political activist to challenging these realities. This volume brings together the reflections of a group of activists and scholars on the significance of Neville Alexander to the cause of freedom and justice in South Africa. The reflections are essentially the keynote speeches and the responses to them that were made at a conference in Alexander's honour held at the Centre for Non-Racialism and Democracy at the Nelson Mandela Metropolitan University in July 2013.